Ответ:
-5
Объяснение:
Домножим обе части на 10
2(x-1) - 8(5-2x) + 120 = -11(4-x) + 87
2x-2-40+16x +120 = -44+11x+87
18x+78 = 43+11x
7x = -35
x = -5
0,2x-0,2-4+1,6x+12=-4,4+1,1x+8,7
0,2x+1,6x-1,1x=-4,4+8,7+0,2+4-12
0,7x=-2,5
x=-25/7
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
-5
Объяснение:
Домножим обе части на 10
2(x-1) - 8(5-2x) + 120 = -11(4-x) + 87
2x-2-40+16x +120 = -44+11x+87
18x+78 = 43+11x
7x = -35
x = -5
Ответ:
0,2x-0,2-4+1,6x+12=-4,4+1,1x+8,7
0,2x+1,6x-1,1x=-4,4+8,7+0,2+4-12
0,7x=-2,5
x=-25/7
Объяснение: